Phytotoxic Residual Effects of Herbicides on Growth and Yield of Mustard (Brassica juncea L.) in Pulse-based Cropping Systems in Arid Regions - Nand Kishore Jat; D.V. Singh (Annals of Arid Zone, 2024)
In this study, the phytotoxic effects of eleven residual herbicide treatments were investigated on growth and yield of mustard (Brassica juncea L.). These treatments included various concentrations of imazethapyr, imazethapyr-based mixtures, and clodinafop-propargyl combined with sodium acifluorfen were applied on preceding crop of mung bean. Our aim was to how the influence of residual effect these herbicides was assess on the growth and overall productivity of mustard. Results indicated that imazethapyr-containing treatments (50 to 125 g a.i. ha-1) significantly inhibited mustard growth, with reductions in shoot length (26.0 to 46.2%) at 30 days after sowing (DAS) and up to 63.4% growth inhibition by 45 DAS, along with 59.3 to 67.0% decrease in seed yield. Conversely, post emergence treatments with clodinafop-propargyl + sodium acifluorfen (187.5 to 312.5 g a.i. ha-1) performed statistically at par with control treatment in plant height, dry matter, and seed yield, making it a safer PoE herbicide for kharif pulse-mustard rotations in arid regions.